2022
DOI: 10.3389/fphar.2022.908830
|View full text |Cite
|
Sign up to set email alerts
|

Momordica charantia Exosome-Like Nanoparticles Exert Neuroprotective Effects Against Ischemic Brain Injury via Inhibiting Matrix Metalloproteinase 9 and Activating the AKT/GSK3β Signaling Pathway

Abstract: Plant exosome-like nanoparticles (ELNs) have shown great potential in treating tumor and inflammatory diseases, but the neuroprotective effect of plant ELNs remains unknown. In the present study, we isolated and characterized novel ELNs from Momordica charantia (MC) and investigated their neuroprotective effects against cerebral ischemia-reperfusion injury. In the present study, MC-ELNs were isolated by ultracentrifugation and characterized. Male Sprague–Dawley rats were subjected to middle cerebral artery occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…At 24 h post reperfusion, 0.1 ml of 4% Evans blue mixed in 0.9% saline was administered intravenously. A quantitative assay using Evans blue was performed to determine blood–brain barrier (BBB) leakage based on a method described previously [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…At 24 h post reperfusion, 0.1 ml of 4% Evans blue mixed in 0.9% saline was administered intravenously. A quantitative assay using Evans blue was performed to determine blood–brain barrier (BBB) leakage based on a method described previously [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The persistent bleeding from a hemorrhagic stroke causes oxidative stress, neuroinflammation, apoptosis, and BBB disruption [ 56 , 70 ]. In addition, the PI3K/Akt/mTOR pathway can modulate multiple cellular and molecular events including oxidative stress factors, inflammatory responses, programmed cell death, and cell survival, and it protects neurons and the brain from ischemic damages [ 9 , 74 , 75 ]. Hence, this pathway can be considered as one a significant signaling pathway and therapeutic target for neuroprotection against stroke.…”
Section: Neurodegenerative Diseases Neurological Disorders and Exosom...mentioning
confidence: 99%
“…From these studies, it can be inferred that PDENs control inflammation from the transcriptional levels of mRNA, as some of these studies reported a lowered level of mRNA in various inflammatory markers. PDENs inhibit various intracellular signaling, such as AKT, GSK3β [ 190 ], TCF4, Nrf2 [ 200 ], NF-κB [ 185 ], and AhR [ 187 ], leading to altered transcriptional signaling and modulated downstream protein expressions. De Robertis et al (2020) and Yin et al (2022) reported hindered mRNA level of TNF-α, IL-1β, IL1R1, IL-6, IL-8, MAPK1, ICAM1, TLR8, HMOX1, and NFR1 after PDENs administration [ 195 , 202 ].…”
Section: Biomedical Applications Of Pdensmentioning
confidence: 99%